Spain : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper analyzes the conduct of fiscal policy in Spain, made topical by the entry into effect of the Budgetary Stability Law in 2003. This law, along with the new permanent financing arrangements with the subnational levels of government, provides a new institutional and legal framework for fiscal policy. These innovations aim to lock in the gains in fiscal consolidation represented by the achievement of the goals of the Stability and Growth Pact in 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet